PENGARUH AKTIVITAS PEMASARAN MELALUI MEDIA SOSIAL TIKTOK TERHADAP KEPUTUSAN PEMBELIAN ULANG KONSUMEN PADA UMKM COFFEE KELANA - Juwita Handayani; Lilis Saryani; Ahmad Sayuti Pulungan; Abdelina (Jurnal Transformasi Pendidikan Indonesia, 2026)
This study examines the relationship between marketing activities on TikTok and repurchase decisions at the "Kelana" coffee shop, an MSME (Micro, Small, and Medium Enterprise). The evolution of social media has transformed TikTok from a mere source of entertainment into a promotional tool capable of capturing customer attention and fostering engagement. Amidst increasingly fierce competition in the coffee shop industry, digital marketing has emerged as a key strategy for retaining customers and encouraging repeat purchases. "Kelana" coffee shop utilizes TikTok to showcase its products, ambiance, and promotions, while also engaging with its audience. However, it remains unclear whether these marketing activities are linked to customer repurchase decisions. Therefore, this study aims to investigate the relationship between TikTok marketing activities and repurchase decisions at "Kelana" coffee shop. The study focuses on two variables: marketing activities on TikTok and repurchase decisions. Marketing activities are assessed based on content format, posting consistency, and audience interaction. Meanwhile, repurchase decisions are evaluated based on customers' willingness to make repeat purchases and their continued preference for "Kelana" coffee shop. A quantitative research method employing a survey approach was used. Data were collected by distributing questionnaires to "Kelana" coffee shop customers who had viewed or interacted with the business's TikTok account. The data were then analyzed using statistical techniques to determine the relationship between the variables. The findings are expected to serve as a basis for "Kelana" coffee shop to evaluate and develop more effective digital marketing strategies. Furthermore, this study aims to contribute to the body of knowledge regarding digital marketing and consumer behavior, specifically concerning the use of TikTok to drive customer repurchases.